Sobre el modo de producción de las artes. Marx y el trabajo productivo - Durán, José María (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
In my contribution “Arte y capital. Releyendo el Capítulo VI (inédito) de El Capital” (Nómadas 13, 2006.1) I outlined a possible link between artistic production and capital by taking into account the notions of ‘production’ and ‘value’ as they are made evident in chapter VI: “Results of the direct production Process”. Here Marx seems to consider that artistic production can only be an unproductive kind of work since it does not involve the production of surplus-value. I resume this discussion by playing closer attention to the paragraph where Marx describes John Milton’s productive activity, and that to underline the crucial difference between productive and unproductive kinds of labour that also characterizes artistic modes of production. I shall conclude my contribution discussing some of these aspects considering how Adolfo Sánchez Vázquez has looked at them.